2022
DOI: 10.3390/nu14112321
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Dyslipidemia in Chinese Adults: A Cross-Sectional Study in Shanghai, China

Abstract: This study examined the association of obesity and dyslipidemia according to body measurements among Chinese adults in Shanghai, a place in the process of rapid urbanization. Using the baseline data of the Shanghai Suburban Adult Cohort and Biobank study (SSACB), the subjects completed questionnaires and physical examinations, and fasting blood was collected for biochemical assays. We estimated the odds ratios (OR) and 95% confidence interval (CI) by multivariable logistic regression. The prevalence was 12.9% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 45 publications
0
14
0
1
Order By: Relevance
“…Another study of Chinese adults showed that obese males also had a higher risk of dyslipidemia than females [29] . This sex disparity may be due to differences in lifestyle between males and females, which are risk factors of dyslipidemia [30] .…”
Section: Discussionmentioning
confidence: 99%
“…Another study of Chinese adults showed that obese males also had a higher risk of dyslipidemia than females [29] . This sex disparity may be due to differences in lifestyle between males and females, which are risk factors of dyslipidemia [30] .…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 , 53 ] Moderate or central obesity subjects have been found to have higher levels of TC, TG, LDL-C, and lower levels of HDL-C compared with nonobese individuals, which may be associated with excess visceral fat in the abdomen. [ 54 , 55 ] There is a strong correlation between overweight or obesity and cardiovascular events and dyslipidemia, and effective control of lipid levels is expected to reduce the incidence of metabolic morbidity and death. [ 56 , 57 ]…”
Section: Discussionmentioning
confidence: 99%
“…[3,53] Moderate or central obesity subjects have been found to have higher levels of TC, TG, LDL-C, and lower levels of HDL-C compared with nonobese individuals, which may be associated with excess visceral fat in the abdomen. [54,55] There is a strong correlation between overweight or obesity and cardiovascular events and dyslipidemia, and effective control of lipid levels is expected to reduce the incidence of metabolic morbidity and death. [56,57] Concerning the biochemical indicators outcomes, our meta-analysis showed large significant improvement in LDL, moderate significant improvement in TG, small significant improvement in TC and HDL of TCE intervention on the biochemical indicators outcomes.…”
Section: Effects Of Tce On Biochemical Indicators Outcomesmentioning
confidence: 99%
“…In 2016, the Joint Committee of Guidelines for the Prevention and Treatment of Dyslipidemia in Chinese Adults reported that the overall prevalence of dyslipidemia in Chinese adults was 40.4%. They projected that the prevalence of dyslipidemia and related disease burden among Chinese adults is expected to increase [11]. Moreover, dyslipidemia in Chinese adults and non-high-density lipoprotein (nonHDL-C) were predicted to be important risk factors of cardiovascular disease [11].…”
Section: Introductionmentioning
confidence: 99%
“…They projected that the prevalence of dyslipidemia and related disease burden among Chinese adults is expected to increase [11]. Moreover, dyslipidemia in Chinese adults and non-high-density lipoprotein (nonHDL-C) were predicted to be important risk factors of cardiovascular disease [11]. NonHDL-C and nonHDL-C / HDL-C (high-density lipoprotein) are now being studied in relation to the occurrence of dyslipidemia [12].…”
Section: Introductionmentioning
confidence: 99%